Pengaruh Citra Perusahaan dan Pemasaran Relasional Terhadap Keputusan Pembelian Mobil - Wiki Nofianada (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
This study aims to find out how the influence of corporate image and relational marketing on consumer purchase decisions. The sample in this study is 78 people who use CV services. Zia car Banda Aceh. This study is a survey research with a quantitative approach, using the multiple linear regression analysis method with the help of the SPSS program. The results of this study show that the corporate image (,X-1.) has a positive influence and a significant level below 0.05, namely (0.00 < 0.05) or ,H-a . is accepted on the consumer's purchase decision (Y) on CV. Zia of Banda Aceh car partially (ttable > tcal value or 4,512 > 1,664). Relational marketing (,X-2.) has a positive influence and a significant level below 0.05 namely (0.015 < 0.05) or ,H-a . is accepted on the consumer's purchase decision (Y) on CV. Zia of Banda Aceh car partially (tcount value > ttable or 2,492 1,664). The most dominant variable has an influence on consumer purchase decisions (Y) on CV. Zia car Banda Aceh is a variable of the company's image (,X-1.) with a ttable > tcount value or 4,512 > 1,664 and the smallest significant value 0.00. The results of the F test show that the variables of company image (,X-1.) and relational marketing (,X-2.) together have a positive and significant effect on consumer purchase decisions (Y) on CV. Zia car Banda Aceh. Based on the results of the research, the author suggests that the quality of service can be improved and maintained so that consumers are not disappointed with the service and consumers will be loyal to continue buying used cars at CV. Zia Car Banda Aceh.